Assessment of human errors in the intensive cardiac care unit nursing profession using the SPAR-H - I Mohammadfam; M Movafagh; A Soltanian; M Salavati; S Bashirian (طب کار)
Background: Quality and safety are two major concerns in the medical professions. According to irreparable consequences arising from human errors in the intensive care unit, the safety level in these sectors is very important. This study aimed to evaluate the human errors in the intensive cardiac care unit nurses. Methods: This research was a qualitative study, conducted by SPAR-H method. In this study, the nursing task was divided into sub-tasks and related activities using a hierarchical task analysis (HTA). The SPAR-H method was used to identify and evaluate human errors. Data were analyzed using SPSS-16 software. Results: Duties include initial resuscitation, saying the code and start cardio-pulmonary resuscitation, shock, intubation and urgent measures for dysrhythmias are critical task with error probability of 0.372, 0.245, 0.233, 0.196 and 0.122/0 respectively. Conclusion: To reduce the rate of human error improving performances shaping factors including decrease of complexity and promote of training as well as modification of nurses shift work and reducing additional duties are recommended.